Incidentally Detected Mediastinal Vascular Anatomical Variants on PET-CT: A Pictorial Essay - Paidipati, Kathyayini Gopalkrishna Murthy; Kashyap, Raghava; Tadimeti, Hima; Peyyeti, Mahidhar
Positron emission tomography with computed tomography (PET–CT) is an integral part of oncology practice in the current-day scenario. The hybrid anatomical and metabolic imaging information in this imaging modality provides access to a wealth of incidental findings which can have implications in the management of the patient, especially when surgical options are being considered. In this pictorial essay, we present incidentally detected mediastinal vascular anomalies on PET–CT, along with a review of associated literature.